2023
DOI: 10.7717/peerj.15690
|View full text |Cite
|
Sign up to set email alerts
|

In silico analysis of serum miRNA profiles in seronegative and seropositive rheumatoid arthritis patients by small RNA sequencing

Abstract: Rheumatoid arthritis (RA) is a refractory autoimmune disease, affecting about 1% of the world’s population. RA is divided into seronegative RA and seropositive RA. However, biomarkers for discriminating between seronegative and seropositive RA have not been reported. In this study, we profiled serum miRNAs in seronegative RA patients (N-RA), seropositive RA patients (P-RA) and healthy controls (HC) by small RNA sequencing. Results indicated that compared with HC group, there were one up-regulated and four down… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Multiple studies have reported miRNAs involved in pro-inflammatory signalling pathways in RA patients leading to increased production of inflammatory cytokines [148][149][150][151]. A recent study by He et al compared different miRNAs between seropositive RA, seronegative RA, and healthy controls [152]. Interestingly, differences between seropositive and seronegative patients were found, with hsa-miR-362-5p more upregulated in the seronegative RA group, and hsa-miR-187-3P and hsa-miR-6855-5p being upregulated in the seropositive group.…”
Section: Peripheral Blood Micrornamentioning
confidence: 99%
“…Multiple studies have reported miRNAs involved in pro-inflammatory signalling pathways in RA patients leading to increased production of inflammatory cytokines [148][149][150][151]. A recent study by He et al compared different miRNAs between seropositive RA, seronegative RA, and healthy controls [152]. Interestingly, differences between seropositive and seronegative patients were found, with hsa-miR-362-5p more upregulated in the seronegative RA group, and hsa-miR-187-3P and hsa-miR-6855-5p being upregulated in the seropositive group.…”
Section: Peripheral Blood Micrornamentioning
confidence: 99%
“…In this regard, it was recently reported that the miRNAs has-miR-362-5p and has-miR-708-3p were upregulated in SNRA but not in SPRA. Other miRNAs were found to be downregulated differently in the two forms of RA, including the mRNAs expressed exclusively in SPRA and others common to both forms [27,28]. Table 1 summarizes the different genetic backgrounds and miRNA expressions between SNRA and SPRA.…”
Section: Pathogenesismentioning
confidence: 99%
“…Table 1 summarizes the different genetic backgrounds and miRNA expressions between SNRA and SPRA. SNP CLYBL High No [26] has-miR-362-5p High Low [27] has-miR-708-3p High Low [28] has-miR-24 High High [30] has-miR-125a High High [30] has-miR-22 Low High [30] has-miR-361-5p Low High [30] has-miR-233-3p Low High [30] SNRA = seronegative rheumatoid arthritis; SPRA = seropositive rheumatoid arthritis; miRNA = microRNA; SNP = single-nucleotide polymorphism.…”
Section: Pathogenesismentioning
confidence: 99%